Systematic Literature Review: Authentic Leadership Practices of School Principals - Prastianingsih, Dwi Ramadani; Hariri, Hasan; Sari, Siti Rahma (Al-Qalam Institue, 2025)
This research examines the role of authentic leadership in fostering trust and collaboration among teachers in Indonesian school environments. By employing the Systematic Literature Review (SLR) method, this research analyses various studies on the application of authentic leadership in the educational context. The research results indicate that school principals who prioritise transparency, integrity, and openness can increase teacher trust and foster a more harmonious work environment. In addition, authentic leadership encourages collaboration between teachers by providing freedom to innovate and share learning strategies. This approach also helps school principals face the challenges of cultural diversity and limited resources through innovative solutions, such as the use of technology and involvement of the school community. Thus, authentic leadership has been proven to contribute to increasing motivation, discipline and the quality of education in Indonesian schools. The implications of this research indicate that implementing authentic leadership can be an effective strategy for increasing teacher trust, collaboration, and motivation in Indonesian schools. Therefore, principals need to develop authentic leadership skills to create a harmonious work environment and encourage quality educational innovation.